The Influence of Work Life Balance on Employee Satisfaction at Grand Hyatt Jakarta Hotel (Case Study of Food and Beverage Service Department Employees) - Tanuputri, Sherina; Nurbaeti, Nurbaeti; Asmaniati, Fetty (Institut Pariwisata Trisakti, 2019)
Work life Balance is a factor that can affect Employees’ Job Satisfaction This study aims to analyze the influence of Work Life Balance on Employee Job Satisfaction in Food and Beverage Service Department at Grand Hyatt Jakarta Hotel. In this study, information was collected from 68 respondents by using questionnaires. The data has been collected, then analyzed by using simple regression analysis with SPSS program. The results of this study indicate that Work life Balance has significant effect on Employee Satisfaction at Food and Beverage Service Department of Grand Hyatt Jakarta Hotel with 0.000 significance level smaller than α (0,050). The effect of Work Life Balance on Employee Job Satisfaction is 22.7%. The results of the highest respondents on the Work Life Balance (Balance of Work Life) is a Balance of Satisfaction of 79% and on Job Satisfaction is about the Appreciation of 82%.